Diversity of actin architecture in human osteoclasts: Network of curved and branched actin supporting cell shape and intercellular micrometer level tubes - Pennanen P; Alanne M; Fazeli E; Deguchi T; Näreoja T; Peltonen S; Peltonen J. (Springer Nature, 2022)
Osteoclasts are multinucleated bone-resorbing cells with a dynamic actin cytoskeleton. Osteoclasts are derived from circulating mononuclear precursors. Confocal and stimulated emission depletion (STED) super-resolution microscopy was used to investigate peripheral blood-derived human osteoclasts cultured on glass surfaces. STED and confocal microscopy demonstrated that the actin was curved and branched, for instance, in the vicinity of membrane ruffles. The overall architecture of the curved actin network extended from the podosomes to the top of the cell. The other novel finding was that a micrometer-level tube containing actin bridged the osteoclasts well above the level of the culture glass. The actin filaments of the tubes originated from the network of curved actin often surrounding a group of nuclei. Furthermore, nuclei were occasionally located inside the tubes. Our findings demonstrated the accumulation of c-Src, cortactin, cofilin, and actin around nuclei suggesting their role in nuclear processes such as the locomotion of nuclei. ARP2/3 labeling was abundant at the substratum level of osteoclasts and in the branched actin network, where it localized to the branching points. We speculate that the actin-containing tubes of osteoclasts may provide a means of transportation of nuclei, e.g., during the fusion of osteoclasts. These novel findings can pave the way for future studies aiming at the elucidation of the differentiation of multinucleated osteoclasts.